PERBANDINGAN AKTIVITAS ANTIOKSIDAN DAN TOKSISITAS ANTARA DAGING BUAH, KULIT BAGIAN DALAM DAN KULIT BAGIAN LUAR BUAH MANGGIS ( GARCINIA MANGOSTANA L.) - yanti, dharma (Jurnal Ayurveda Medistra, 2021)
Abstract Mangosteen (Garcinia mangostana L.) is a fruit that has the potential to have medicinal properties and has been used in empirical treatment (experience). Based on previous experiments, mangosteen rind contains xanthones which have antioxidant, anti-tumor, anti-inflammatory, anti-allergenic, antibacterial, anti-fungal, anti-malarial and anti-cancer activities. Previous experiments focused more on the skin, but no one has tested and compared the activity of the fruit parts. This experiment aims to compare the antioxidant activity and toxicity between the pulp, inner skin and outer skin of the mangosteen fruit. This is intended to determine the best antioxidant activity and toxicity between the three parts of the mangosteen fruit so that it can be used as a basis for further testing of their activity as an ingredient Antioxidant activity testing was carried out using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) free radical reduction method. A substance is declared to have antioxidant activity if the IC50 value is <150µg / ml, the smaller the IC50, the stronger the antioxidant activity. In the toxicity test of a substance it is said to be toxic if the LC50 is <1000 µg / ml, the smaller the LC50 value, the stronger the toxicity. The toxicity test was carried out by the Brine Shrimp Lethality Test (BSLT) method using Artemia salina L. shrimp larvae. Antioxidant test results were statistically processed using linear regression to obtain the IC50 value, while the results of the toxicity test were processed by computerized probit analysis using SPSS 14 software for windows to determine the LC50 value. Based on the antioxidant activity testing, it was concluded that the three samples had the potential for antioxidant activity with IC50 values ​​respectively, 1.95 µg / ml (outer shell extract); 7.00 µg / ml (inner skin extract); 51.10 µg / ml (mangosteen pulp extract). Based on the results of the toxicity test, the LC50 values ​​of the samples were respectively 6.29 µg / ml (inner shell extract); 9.17 µg / ml (outer skin extract) and 1158.47 µg / ml (mangosteen pulp extract), so it can be concluded that the toxic parts are the outer and inner skin parts while the mangosteen fruit is not toxic.